Novel Method of Analysis for the Determination of Residual Formaldehyde by High-Performance Liquid Chromatography - Vittoria Delbono; Christopher P. Larch; Katrina Carol Newlands; Shona Rhydderch; Thomas Craven Baddeley; John Mervyn David Storey (International Journal of Analytical Chemistry)
Formaldehyde is commonly used as an alkylating agent in the pharmaceutical industry. Consequently, its residual level in drug substances and/or their intermediates needs to be accurately quantified. Formaldehyde is a small, volatile molecule with a weak chromophore (the carbonyl group), and its direct analysis by GC-FID and HPLC-UV is difficult. For these reasons, the majority of papers found in the literature are based upon a derivatisation process (most commonly using the desensitised explosive 2,4-dinitrophenylhydrazine) prior to the analysis of formaldehyde. A novel high-performance liquid chromatography (HPLC) method with UV detection for its quantification in a pharmaceutical is described in this paper. The method proposed herein is based upon a derivatisation reaction between formaldehyde and 4-methylbenzenesulfonohydrazide (MBSH) before analysis by HPLC-UV. Selectivity, linearity, limit of quantification, accuracy, repeatability, intermediate precision, and solution stability were successfully assessed as per ICH guideline Q2(R1), and the method has also been validated in a good manufacturing practice (GMP) laboratory in the UK.